Perception of Eco-innovation Based on Educational Attainment - Erika Loučanová; Vladislav Kaputa; Miriam Olšiaková (European Management Studies)
Aim: To evaluate the influence of educational attainment on the perception of ecological innovation was the main objective of the paper. The depth of attention paid to the interdisciplinary impact of innovations and education in society ultimately affects the level of the culture of education and whether the innovations that arise respect people and their environment. Design/methodology/approach: Input data gathered via survey of customers using the Kano questionnaire. The research applied the Kano model to data processing. The analysis allowed us to measure and explore the emotional reactions of Slovak customers to products. Findings: If multidisciplinary innovations positively affect the environmental, economic, and social development of society, they also tend to increase competitiveness of regions and lead to sustainability, development, and the knowledge economy. It can be concluded that the level of education achieved affects attitudes towards ecological innovation. The higher the education level of the respondents, the more sensitively they perceived the issue of eco-innovation. The interpretation of the results is a contribution to the discussion about the importance of education with an interdisciplinary overlap, as well as a view on innovation that respects individuals, society, and the environment. Research limitations/implications: Even though the results demonstrate the influence of the attitudes of Slovak customers depending on their educational attainment, it is necessary to verify whether they are reflected in real purchasing behavior. Originality/value: The originality of the research lies in the methodical approach of connecting the perception of ecological product innovations and the socio-demographic aspect (educational attainment) in the market conditions of the Slovak Republic.